Medievalism in contemporary opera - Haggett, GK (2024)
This thesis discusses four operas, all written after 1990, that are based on medieval texts: Caritas (1991, by Robert Saxton and Arnold Wesker), The Tale of Januarie (2017, by Julian Philips and Stephen Plaice), L’Amour de loin (2000, by Kaija Saariaho and Amin Maalouf), and Gawain (1991, by Harrison Birtwistle and David Harsent). Each case study is approached as an adaptation of a different medieval literary genre: affective piety, the fabliau, the troubadour lyric, and the chivalric romance. This organizational method provides a point of access into the cultural, critical, and creative reception histories through which texts from the twelfth-to-fourteenth centuries are received by composers, librettists, performers, readers, and audiences today.